C-terminal processing of the teneurin proteins: Independent actions of a teneurin C-terminal associated peptide in hippocampal cells - Chand, Dhan; Casatti, Cláudio Aparecido [UNESP]; de Lannoy, Louise; Song, Lifang; Kollara, Alexandra; Barsyte-Lovejoy, Dalia; Brown, Theodore J.; Lovejoy, David A. (Elsevier, 2013)
Many neuropsychiatric conditions have a common set of neurological substrates associated with the integration of sensorimotor processing. The teneurins are a recently described family of proteins that play a significant role in visual and auditory development. Encoded on the terminal exon of the teneurin genes is a family of bioactive peptides, termed teneurin C-terminal associated peptides (TCAP), which regulate mood-disorder associated behaviors. Thus, the teneurin-TCAP system could represent a novel neurological system underlying the origins of a number of complex neuropsychiatric conditions. However, it is not known if TCAP-1 exerts its effects as part of a direct teneurin function, whereby TCAP represents a functional region of the larger teneurin protein, or if it has an independent role, either as a splice variant or post-translational proteolytic cleavage product of teneurin. In this study, we show that TCAP-1 can be transcribed as a smaller mRNA transcript. After translation, further processing yields a smaller 15. kDa protein containing the TCAP-1 region. In the mouse hippocampus, immunoreactive (ir) TCAP-1 is exclusively localized to the pyramidal layers of the CA1, CA2 and CA3 regions. Although the localization of TCAP and teneurin in hippocampal regions is similar, they are distinct within the cell as most ir-teneurin is found at the plasma membrane, whereas ir-TCAP-1 is predominantly found in the cytosol. Moreover, in mouse embryonic hippocampal cell culture, FITC-labeled TCAP-1 binds to the plasma membrane and is taken up into the cytosol via dynamin-dependent caveolae-mediated endocytosis. Our data provides novel evidence that TCAP-1 is structurally and functionally distinct from the larger teneurins. © 2012.
Keywords: Caveolin; Hippocampus; Neuropeptide; Peptide-processing; Stress; Teneurin; messenger RNA; neuropeptide; teneurin; teneurin carboxyl terminal associated peptide 1; teneurin carboxyl terminal associated peptide derivative; unclassified drug; animal cell; carboxy terminal sequence; cytosol; embryo; endocytosis; hippocampal CA1 region; hippocampal CA2 region; hippocampal CA3 region; male; mood disorder; mouse; nonhuman; nucleotide sequence; priority journal; protein degradation; protein localization; protein processing; RNA transcription; RNA translation; Amino Acid Sequence; Animals; Blotting, Northern; Blotting, Western; Fluorescent Antibody Technique; Immunohistochemistry; Male; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Nerve Tissue Proteins; Polymerase Chain Reaction; Protein Biosynthesis; Pyramidal Cells; Tenascin; Transcription, Genetic